2023
DOI: 10.3390/cancers15133280
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Next-Generation Sequencing in Diagnosis, Prognosis and Therapeutic Management of Acute Myeloid Leukemia/Myelodysplastic Neoplasms

Abstract: For decades, the diagnosis, prognosis and thus, the treatment of acute myeloblastic leukemias and myelodysplastic neoplasms has been mainly based on morphological aspects, as evidenced by the French-American-British classification. The morphological aspects correspond quite well, in a certain number of particular cases, to particular evolutionary properties, such as acute myelomonoblastic leukemias with eosinophils or acute promyelocytic leukemias. Advances in biology, particularly “classical” cytogenetics (ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, a multiplexed single cell transcriptomic study has demonstrated its potential in assessing the sensitivity of leukemic cells to chemotherapy while elucidating underlying mechanisms [ 40 ]. Integrating the cell hashing technique with genetic and phenotypic approaches will facilitate the identification of distinct leukemic cell sub-populations, the discovery of new diagnostic and prognostic markers, and the establishment of targeted therapies for personalized clinical management of acute myeloid leukemia patients [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a multiplexed single cell transcriptomic study has demonstrated its potential in assessing the sensitivity of leukemic cells to chemotherapy while elucidating underlying mechanisms [ 40 ]. Integrating the cell hashing technique with genetic and phenotypic approaches will facilitate the identification of distinct leukemic cell sub-populations, the discovery of new diagnostic and prognostic markers, and the establishment of targeted therapies for personalized clinical management of acute myeloid leukemia patients [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…qPCR methods can be used to monitor other molecular markers, such as FLT3-ITD and the overexpression of WT1, which are relatively common genetic abnormalities in AML: FLT3-ITD is present in 25% of adult AML cases [66], and nearly 75% of AML cases overexpress WT1 [67]. The increasing use of targeted therapies such as gilteritinib or midostaurin (tyrosine kinase inhibitors targeting FLT3 and other kinases) in FLT3-mutated AML makes the monitoring of this marker even more enticing.…”
Section: Molecular Approachesmentioning
confidence: 99%
“…Another challenge when monitoring molecular MRD by NGS is distinguishing between leukemia driver mutations, which are associated with relapse, and clonal hematopoiesis-associated mutations [22,79]. Indeed, as hematopoietic cells can acquire somatic mutations in the absence of hematological malignancy (i.e., clonal hematopoiesis of indeterminate potential (CHIP)) and this state of clonal hematopoiesis can be a precursor state of AML, CHIP-associated mutations such as DNMT3A, TET2, and ASXL1 (DTA mutations) often persist at high levels at cytological remission of AML without being associated with any prognostic value or higher risk of relapse [26,66]. For instance, Jongen-Lavrencic et al [26], in their cohort of 482 patients with AML, highlighted the persistence of mutations after induction therapy in 51.4% of cases, among which DTA mutations were more frequent, often detected with high VAFs (up to 47%), and not associated with an increased relapse risk.…”
Section: Next-generation Sequencingmentioning
confidence: 99%